Simulation and Analysis of Battery Pack Using the Multi Scale Multi-Domain Battery Model - Ravikant Nanwatkar; Pravin Nitnaware; Aparna Bagde (International Journal of Electro-Mechanics and Material Behaviour, 2024)
The creation of sophisticated simulation models has been made necessary by the need for reliable and effective battery packs in energy storage systems and electric vehicles. This study focuses on the simulation and analysis of battery packs using a multi-scale multi-domain battery model. The model enables a thorough knowledge of battery pack behavior across a range of operating situations by integrating the electricity, thermal, and mechanical domains. Multi-scale modeling bridges the micro-level electrochemical processes with macro-level pack performance, enabling the prediction of key parameters such as temperature distribution, state of charge (SOC), and degradation patterns. A robust simulation framework is developed to evaluate the impact of environmental factors, dynamic load conditions, and thermal management strategies on battery pack efficiency and lifespan. The results demonstrate significant improvements in accuracy over conventional single-domain models, particularly in predicting thermal runaway scenarios and ensuring optimal energy utilization. This research highlights the potential of multi-scale multi-domain modeling as a critical tool for designing next-generation battery packs with enhanced performance, safety, and durability. The findings serve as a valuable resource for engineers and researchers in optimizing battery systems for electric vehicles and renewable energy applications. The goal of future development was to incorporate immediate information for analytical storage and improved system consistency.
Keywords: Simulation; State of Charge; Temperature Distribution; battery packs; electric vehicles; multi-scale multi-domain model